Consumer motivation for organic food consumption: Health consciousness or herd mentality - Jiangbo Wang; Yefei Xue; Tingting Liu (Frontiers Media S.A., 2023)
Whether health awareness is self-awareness or conformity awareness is a question worth discussing. Especially under the current trend of organic food consumption, whether it is driven by health consciousness or herd mentality is worth exploring. This is not only about the government's formulation of health policies for the industry (for example, paying more attention to health standards), but also about the sustainable development of organic food consumption (for example, suppliers highlighting their own health advantages). However, there is still little research in this area. Based on data from 1,658 respondents in four first-tier cities in China, this paper explores whether consumers are consuming organic food under health consciousness or herd mentality. This paper uses a logit model to explore the key causes of health consciousness or herd mentality, and uses a propensity score matching (PSM) method to measure the impact of health consciousness and herd mentality on organic food consumption, comparing the effects across age and education groups. The results show that: (1) Individual characteristics, family characteristics, health status, volition, social trust and market education significantly influenced consumers' health consciousness or herd mentality; (2) The main motivation for organic food consumption is health consciousness, but herd mentality plays a role of amplifying this effect.